Risk and protective factors in dancers exposed to trauma - Thomson, P.; Jaque, S. V. (Journal of Dance Medicine & Science, 2024)
Purpose: This study examined risk and protective factors in dancers with/without posttraumatic stress disorder (PTSD) and with/without trauma exposure.